2011
DOI: 10.21273/hortsci.46.7.1027
|View full text |Cite
|
Sign up to set email alerts
|

Drought Tolerance Associated with Proline and Hormone Metabolism in Two Tall Fescue Cultivars

Abstract: Drought stress is a major factor in turfgrass management; however, the underlying mechanisms of turfgrass drought tolerance are not well understood. This greenhouse study was designed to investigate proline and hormone responses to drought stress in two tall fescue [Festuca arundinacea (Schreb.)] cultivars differing in drought tolerance. The two cultivars, Van Gogh (relatively drought-tolerant) and AST7002 (relatively drought-sensitive), were established and grown under eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
94
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 33 publications
14
94
2
Order By: Relevance
“…For example, it has been reported that ZR can improve tolerance against heat and water stress in some herbaceous species such as Agrotis stolinifera L. and Festuca arandinacea (Schreb.) (Veerasamy et al, 2007;Man et al, 2011). In accordance with these works, our results demonstrate that ZR is a relevant CK which can also enhance drought tolerance in some gymnosperms like P. radiata and could be used as stress resistance indicator.…”
Section: Discussionsupporting
confidence: 87%
“…For example, it has been reported that ZR can improve tolerance against heat and water stress in some herbaceous species such as Agrotis stolinifera L. and Festuca arandinacea (Schreb.) (Veerasamy et al, 2007;Man et al, 2011). In accordance with these works, our results demonstrate that ZR is a relevant CK which can also enhance drought tolerance in some gymnosperms like P. radiata and could be used as stress resistance indicator.…”
Section: Discussionsupporting
confidence: 87%
“…Cytokinin and ABA are closely associated with plant tolerance to water deficit (Taiz and Zeiger, 2010; Man et al, 2011). In our study, we found that water deficit reduced leaf iPA content and increased ABA content.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence showing that plant physiological fitness is largely governed by hormonal balance (Itai, 1999; Zhang et al, 2009). It has been documented that indoleacetic acid (IAA) is associated with root development and growth (Zhang et al, 2009; Man et al, 2011). A recent study has shown that leaf tissue IAA content was positively correlated with drought tolerance and IAA content increased as plants adapted to drought stress (Man et al, 2011).…”
mentioning
confidence: 99%
“…It has been documented that indoleacetic acid (IAA) is associated with root development and growth (Zhang et al, 2009; Man et al, 2011). A recent study has shown that leaf tissue IAA content was positively correlated with drought tolerance and IAA content increased as plants adapted to drought stress (Man et al, 2011). Abscisic acid (ABA), another important hormone, is also thought to play an important role in the adaptation of cassava ( Manihot esculenta Crantz) to environmental stress (Alves and Setter, 2004).…”
mentioning
confidence: 99%